O-015 Cost-effectiveness of vertebroplasty and kyphoplasty vs non-surgical management for symptomatic vertebral compression fractures in the USA. (12th July 2011) - Win, S; Do, H
Abstract : Introduction and Purpose: Vertebroplasty (VP) and Kyphoplasty (KP) are minimally invasive surgical procedures which can relieve the pain of osteoporotic vertebral compression fractures (VCFs) and increase the functionality of patients, as supported by a number of recent randomized controlled trials. VCFs can present with debilitating back pain, uncontrolled by pain medications, that can seriously impede activities of daily living and lead to additional morbidity and mortality. The purpose of this study is to perform a cost-effectiveness analysis comparing VP, KP, and non-surgical management (NSM or conservative medical therapy) for US patients with painful VCFs. Materials and Methods: A Markov transition state model was created with three treatment strategies: VP, KP, and NSM. A hypothetical cohort of 70-year-old men and women was followed for 30 years or until death. Inputs for the model originated from the published medical literature. Health outcomes were measured in quality-adjusted life years. The economic outcome measure of the model was the difference in healthcare costs among the three treatment strategies. Deterministic 1-way and probabilistic sensitivity analyses were performed to test the robustness of the model. Results: VP and KP both dominated NSM. When VP and KP were compared, VP was preferred with an incremental cost savings of US$75 000 per quality-adjusted life years gained. Overall, VP was the preferred treatment strategy for symptomatic VCFs. 1-way sensitivity analyses comparing NSM to VP and NSM to KP showed that the cost of physical therapy after NSM was the variable most sensitive to the incremental cost-effectiveness ratio. At willingness to pay of US$50 000, VP was the preferred strategy with probability of 100%. This preference extended to willingness to pay US$25K and US$100K, respectively. Conclusion: The balance of costs and effectiveness favors Vertebroplasty. This favors, from a societal perspective, VP as the preferred treatment strategy for painful osteoporotic VCFs.